Reflection Of 'Care' Culture As An Identity At Rsud Dr. Drajat Prawiranegara Serang - Noerma Kurnia Fajarwati; Eka Susilawati; Opiq Piqhi (LEGAL BRIEF, 2022)
RSUD dr Drajat Prawiranegara or RSDP Serang has a noble goal to become the best hospital with professional and quality services as stated in the vision of the organization. As one of the referral hospitals, RSDP Serang has an organizational culture value, namely Cakap – Accountable – Responsive – Efficient which is abbreviated as 'CARE'. This study aims to explain the application of CARE culture as an organizational identity at RSDP Serang. The research was conducted by the quantitative, descriptive univariate method. A sample of 146 people was taken, consisting of general employees and health workers. This research shows that the application of CARE culture is still not optimal, so it has not fully reflected the identity of Serang Hospital as a superior quality hospital in Banten Province. It takes responsibility for all elements in the hospital, especially employees, both those who serve as health and non-health workers, to create public trust and organizational identity.